Viscoelasticity of Short Polymer Liquids from Atomistic Simulations. Issue 9 (23rd May 2019) - David, Alessio; De Nicola, Antonio; Tartaglino, Ugo; Milano, Giuseppe; Raos, Guido
Abstract : The viscosity − or more generally the viscoelasticity − of polymer liquids is a key property for the processing as well as the performance of these materials. Molecular theories and numerical methods can provide these quantities, but they all require certain input parameters that nowadays are typically obtained by experiment. In the long term, it would be desirable to obtain these parameters or the whole viscoelastic response by purely computational methods, enabling a full "in silico" design of new materials and processes. In this perspective, we present several test calculations of the viscosity of n -hexadecane, a short-chain analogue of polyethylene. Our calculations are based on both equilibrium and non-equilibrium molecular dynamics (MD) simulations, which are applied to models based on a united-atom force field, a conventional atomistic force field, and the AIREBO-M reactive force field. We compare both the computational cost of the different strategies and the reliability of the different models and we provide some general guidelines for their application to more complex systems.